2022
DOI: 10.1001/jamanetworkopen.2022.2599
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Machine Learning–Based Medical Directives to Expedite Care in Pediatric Emergency Medicine

Abstract: IMPORTANCEIncreased wait times and long lengths of stay in emergency departments (EDs) are associated with poor patient outcomes. Systems to improve ED efficiency would be useful. Specifically, minimizing the time to diagnosis by developing novel workflows that expedite test ordering can help accelerate clinical decision-making. OBJECTIVE To explore the use of machine learning-based medical directives (MLMDs) to automate diagnostic testing at triage for patients with common pediatric ED diagnoses. DESIGN, SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted 19 22 . Like the Transparent reporting of a multivariable prediction model for individual prognosis or diagnosis (TRIPOD) or The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for reporting machine learning results 23 , 24 , there should be a guideline for the standardization of user interfaces (UIs) and a format for clinical decision support for end-users, including clinicians and patients 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted 19 22 . Like the Transparent reporting of a multivariable prediction model for individual prognosis or diagnosis (TRIPOD) or The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for reporting machine learning results 23 , 24 , there should be a guideline for the standardization of user interfaces (UIs) and a format for clinical decision support for end-users, including clinicians and patients 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22] . Like the Transparent reporting of a multivariable prediction model for individual prognosis or diagnosis (TRIPOD) or The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for reporting machine learning results 23,24 , there should be a guideline for the standardization of user interfaces (UIs) and a format for clinical decision support for end-users, including clinicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“… Emergency department testing: Singh et al reported an ML model to predict the need for frequently performed clinical testing (urinary dipstick testing, electrocardiogram, abdominal ultrasonography, testicular ultrasonography, bilirubin level testing, and forearm radiographs) among children presenting to a pediatric emergency department. 34 Using an outcome of testing ordered in triage, the model demonstrated high area under the receiver operating characteristic curve (AUROC) (0.89–0.99, across individual use cases for clinical tests including urinary dipstick testing and electrocardiograms) with a high positive predictive value (0.77–0.94) with results available by a mean time of 165 min. The investigators were further able to characterize model explainability using Shapley Additive Explanation to ensure their clinical relevance.…”
Section: Ai and Predictive Modelingmentioning
confidence: 99%